Development of Human Resource Competencies for Indonesian Migrant in Malaysia (Perspective on Analyzing Human Resource Needs in The Digital Era) - AWALI, HUSNI; Rohmah, Farida (Jurnal Ekonomi dan Bisnis Indonesia, 2025)
This study aims to analyze the development of human resource competencies for Indonesian migrant workers in Malaysia, particularly in addressing the challenges of the digital era. The rapidly evolving digital era has brought significant changes to the labor market, affecting both traditional and digital industry sectors. As a result, Indonesian migrant workers are required to acquire new competencies to remain competitive and adapt to these changes. This research employs a qualitative approach, with data collected through in-depth interviews and literature reviews. The focus of the study is to identify the competencies needed in sectors impacted by digitalization, the differences in competencies between traditional and digital sectors, the challenges faced in competency development, and the role of governments and training institutions in supporting this process. The findings indicate that Indonesian migrant workers need to enhance their competencies, particularly in digital and technological skills, to survive in Malaysia’s increasingly competitive labor market. The challenges encountered include limited access to training, educational gaps, and language barriers. Governments and training institutions, both in Indonesia and Malaysia, play a crucial role in providing training programs relevant to modern industry needs. The study concludes with recommendations for competency development strategies, including improving access to technology training, fostering collaboration between the public and private sectors, and providing continuous education programs. It is hoped that this research can serve as a reference for governments, educational institutions, and related parties in formulating effective policies for the development of competencies among Indonesian migrant workers in the digital era.